2016
DOI: 10.5604/15093492.1198829
|View full text |Cite
|
Sign up to set email alerts
|

Use of Autologous Serum in Treatment of Lumbar Radiculopathy Pain. Pilot Study

Abstract: STRESZCZENIEWstęp. Ce lem ba da nia by ło okre śle nie przy dat no ści te ra pii z za sto so wa niem wła snej su ro wi cy u pa cjen tów z obja wa mi uci sko wy mi ko rze nia w prze bie gu dys ko pa tii od cin ka lę dźwio we go. Za sto so wa no te ra pię opar tą na Au to logicz nej Kon dy cjo no wa nej Su ro wi cy (Au to lo gic Con di tio ned Se rum, ACS, Or tho ki ne).Ma te riał i me to dy. U 15 pa cjen tów z jed no po zio mo wą prze pu kli ną ją dra mia żdży ste go po twier dzo ną ob ra zem MRI, z ob ja wa mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…This study showed significant improvement in pain and disability in 13 patients, two of them underwent surgery due to increased pain, and no radicular damage was reported. The authors concluded ACS can be a potential treatment for radicular compression, although many further stronger studies are required on this subject [ 12 ].…”
Section: Radiculopathiesmentioning
confidence: 99%
“…This study showed significant improvement in pain and disability in 13 patients, two of them underwent surgery due to increased pain, and no radicular damage was reported. The authors concluded ACS can be a potential treatment for radicular compression, although many further stronger studies are required on this subject [ 12 ].…”
Section: Radiculopathiesmentioning
confidence: 99%
“…It is possible to administer ACS, periarticularly, intraarticularly, periradicularly and even epidural in up to 6 doses of 3-4ml. 20,21 The injection technique is identical to the one described above, however, it should be remembered that intradiscally is delivered only part of the dose obtained after centrifugation with 10ml of whole blood, i.e. approx.…”
Section: Acs (Orthokine) Treatment Under Ct Controlmentioning
confidence: 99%
“…Autologous conditioned serum (ACS) or also called autologous cytokine rich serum (ACRS) was developed in the mid1990s as an expeditious, practical, and relatively inexpensive means of generating the interleukin-1 receptor antagonist (IL-1Ra), a naturally occurring inhibitor of the cytokine interleukin-1 (IL-1) [9][10][11][12]. The safety pro le of autologous conditioned serum is proven [13,14].…”
Section: Introductionmentioning
confidence: 99%